Masalah Internalisasi dan Persepsi Dukungan Sosial Keluarga pada Remaja - Sari, Tri Purnama; Widyasari, Dian Caesaria; Karmiyati, Diah; Syakarofath, Nandy Agustin (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
The purpose of this study was to investigate the relationship between perceived family social support and internalizing problems among adolescents through a correlational, quantitative study. A total of 689 adolescents in Muhammadiyah senior high school, aged between 15 and 18 years, who resided with their family and/or parents in the East Java Province (Indonesia) were recruited through a simple random sampling. The study used the Perceived Social Support-Family (PSS-Fa) scale and the Strength and Difficulties Questionnaire (SDQ). Linear regression indicated a significant relationship between perceived family social support towards adolescent internalizing problems. This finding confirms the notable role of parents in preventing internalizing problems in adolescence.